The role of social media in realizing accountability for the implementation of E-Governance - Harmono, Fendi (Universitas Wiralodra, 2024)
The digital era has brought convenience in various fields, including in the administration of government. Delivery of information on various programs, policies, and various service activities organized by the government is disseminated through social media. However, in practice, many challenges and problems are encountered by Government Institutions in planning and managing social media as a form of implementing e-governance. This research presents various theories about social media, how the role of social media in the implementation of e-governance, and theories about accountability for the implementation of e-governance. Literature Review is the method chosen in this study to identify, evaluate, and interpret previous studies that are relevant to research questions, research topics, and phenomena of concern. A qualitative approach (data extraction) is used to summarize research results and describe findings. This study reviews the use of social media by Government Institutions, namely the interaction between the government and the community, how the community gets the opportunity to express opinions, questions, and complaints, and ensures that governance is oriented to the interests and needs of the community as a form of accountability. The results of the study show that the use of social media needs to be managed properly to realize the accountability of Government Institutions in providing public services by considering the use of social media utilization models as expressed by experts. There are similarities between STOC culture in the use of social media by government agencies and government accountability.